A modified cyclodextrin, a treatment-free heat-sensitive plate precursor and a treatment-free heat-sensitive plate containing the same, and applications thereof

By using the modified cyclic paste in the non -treatment thermal version, the surface migration problems of infrared absorbers and thermal causes in the imaging layer are solved, and higher image performance and printing resistance are achieved.

CN116655829BActive Publication Date: 2025-01-28LUCKY HUAGUANG GRAPHICS
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202310523044.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-10
Publication Date
2025-01-28
Estimated Expiration
2043-05-10

AI Technical Summary

Technical Problem

In the treatment-free heat-sensitive version technology, infrared absorbers and thermal initiators are prone to surface migration, affecting the initiation efficiency, resulting in problems such as insufficient deep-level initiation, uneven image color, unreal dot reduction and unsolid coating.

Method used

Using modified cycloid essence, this modified cycloid essence is combined with cycloid essence with isocyanate -based acrylate to form aurticated acrylate. A cross -linking response to other components in the imaging layer forms a variety of cross -crossing structures, thereby solving the surface migration problem of infrared absorption agents and thermal cause.

Benefits of technology

Effectively improve the image performance and printing of the thermist version, improve the color uniformity of the image and the restore effect of the outlet, and enhance the firmness of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a modified cyclodextrin and a treatment-free thermal plate precursor and a treatment-free thermal plate containing the same and applications thereof. The modified cyclodextrin is a product obtained by an amination reaction of cyclodextrin (CD) or a cyclodextrin substitute and isocyanate acrylate (ICA), and has a hollow conical cylindrical three-dimensional ring structure. Various organic compounds can be embedded in the hydrophobic cavities of the modified cyclodextrin, and the infrared absorber and the thermal initiator can be effectively adsorbed. At the same time, the modified cyclodextrin after imaging forms a three-dimensional network cross-linked structure, thereby effectively solving the surface migration problem of the infrared absorber and the thermal initiator in the imaging layer; in addition, the modified cyclodextrin forms an urethane bond acrylate through an amination reaction, which has high thermal cross-linking activity and wear resistance, and can effectively improve the imaging performance of the treatment-free thermal plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of advanced lithography technology, and specifically relates to a modified cyclodextrin and a treatment-free thermal plate precursor and a treatment-free thermal plate containing the same and their application. This application belongs to the green printing material of the 3.19 ecological environment material sub-direction under the 3.1 new functional material industry key direction of the 3 new material industry in the catalog of strategic emerging industries. Background Art

[0002] Computer to plate (CTP) is widely used in modern printing. Common CTP plates are divided into photosensitive CTP plates and thermal CTP plates.

[0003] Thermal CTP plate (thermal plate for short) is an offset printing plate that uses infrared laser for imaging. Thermal plates are widely used because they can be operated in bright rooms and have high imaging quality.

[0004] The printing industry is an environmentally unfriendly and highly polluting industry, especially the waste developer produced during the printing process, which causes great harm to the environment. Therefore, the printing industry around the world is advocating the implementation of green printing technology. Green printing technology refers to the use of environmentally friendly materials and process technologies to reduce the pollution generated during the printing process. Developing green and environmentally friendly printing plates is the top priority in the development of green printing.

[0005] Thermal plate technology is constantly improving and developing, and thermal plate materials are also being updated. One of the directions of technological development is to explore green printing technology and develop environmentally friendly, process-free thermal plates.

[0006] There are many technical routes for processing-free thermal plates, which can be divided into thermal ablation technology, phase change technology, hot melt technology, etc. Thermal ablation technology refers to the use of infrared laser energy to ablate the oleophilic coating, exposing the hydrophilic surface of the aluminum plate to form a hydrophilic area; phase change technology refers to the use of laser energy to cause the polymer to undergo a hydrophilic-oleophilic conversion to achieve ink-water separation; hot melt technology refers to the use of laser energy to melt the thermoplastic polymer particles dispersed in the cross-linked hydrophilic layer, changing from hydrophilic to hydrophobic and oleophilic.

[0007] Unprocessed thermal plates can be divided into two categories: (1) Direct-on-press unprocessed thermal plates. After the plate is imaged, it can be directly put on the press and developed and printed under the action of the printing press fountain solution; (2) Low-chemical development type unprocessed thermal plates. After the plate is exposed and imaged on the platemaking machine, no chemical developer is required. It can be developed by washing with clean water and then printed on the press.

[0008] The development of process-free thermal plates, especially the development of process-free thermal plate precursors, is a hot topic in the world today. The process-free thermal plate precursor refers to the precursor for manufacturing process-free thermal plates, and generally refers to the necessary materials and technologies required before manufacturing process-free thermal plates.

[0009] Technology for developing processing-free heat-sensitive plate precursors: WO2013 / 032780 discloses a lithographic printing plate precursor for on-press development; EP0980754 introduces a decarboxylation technology to achieve hydrophilic-hydrophobic conversion; WO94 / 23954 introduces a hot-melt micro-gel technology; US4004924 introduces a mixture of thermoplastic hydrophobic particles and hydrophilic binders; EP 2006-5-2406114475.4 introduces a hot-melt thermoplastic particle; US 2005-8-3 11 / 196,124 introduces a one-dimensional linear structure hydrophilic adhesive; US 2006-7-27 11 / 494,235 introduces a printing plate precursor containing a hydrophilic group and an esterified allyl group, etc.

[0010] There are many technologies used in the processing-free thermal plates. One of the mainstream technologies is to use infrared absorbers to transfer the thermal energy of the laser to the thermal initiator. The thermal initiator triggers the chemical reaction of the thermal sensitive layer to achieve laser imaging.

[0011] As the processing-free thermal plate technology continues to advance, technicians have discovered that infrared absorbers and thermal initiators are very likely to migrate in the image layer. The surface migration problem directly affects the initiation efficiency, resulting in insufficient deep initiation, uneven image color, unrealistic dot restoration, and loose coating.

[0012] The purpose of the present invention is to solve the surface migration problem of infrared absorbers and thermal initiators in the imaging layer, improve the image quality, and further enhance the performance of the processing-free thermal sensitive plate. Summary of the invention

[0013] In order to solve the above problems, the present invention provides a modified cyclodextrin and a treatment-free thermal plate precursor and a treatment-free thermal plate containing the same and applications thereof. The modified cyclodextrin is a product obtained by an amination reaction of cyclodextrin (CD) and isocyanate acrylate (ICA). Since the outer edge (Rim) of the cyclodextrin is hydrophilic and the inner cavity (Cavity) is hydrophobic, it can provide a hydrophobic binding site, which can effectively adsorb infrared absorbers and thermal initiators. At the same time, the modified cyclodextrin after imaging forms a three-dimensional network cross-linked structure, thereby effectively solving the surface migration problem of the infrared absorber and the thermal initiator in the imaging layer; in addition, the modified cyclodextrin forms an amine bond acrylate through an amination reaction, which has high thermal cross-linking activity and wear resistance, and can effectively improve the imaging performance of the treatment-free thermal plate.

[0014] The object of the present invention is achieved in the following manner:

[0015] A modified cyclodextrin, characterized in that the modified cyclodextrin is a product obtained by amination reaction of cyclodextrin (CD) or a cyclodextrin substitute and isocyanate acrylate (ICA).

[0016] Among them, isocyanate acrylate (ICA) has the following structure:

[0017]

[0018] R 1 is a hydrogen atom or a methyl group, R 2 It is an ester group, an aromatic group, an ether group or a covalent bond, and r is an integer of 1-3.

[0019] Cyclodextrin (CD for short) has 6-12 D-pyranose units. Molecules containing 6, 7, and 8 glucose units are called α-cyclodextrin (α-CD), β-cyclodextrin (β-CD), or γ-cyclodextrin (γ-CD), respectively. Cyclodextrin molecules have a slightly conical hollow cylindrical three-dimensional ring structure. In its hollow structure, the larger opening end at the upper end of the outer side is composed of secondary hydroxyl groups of C2 and C3, and the smaller opening end at the lower end is composed of primary hydroxyl groups of C6. It is hydrophilic, and the cavity forms a hydrophobic area due to the shielding effect of the CH bond. Various organic compounds can be embedded in its hydrophobic cavity to form an inclusion complex, which can effectively adsorb infrared absorbers and thermal initiators. In addition, modified cyclodextrin can undergo cross-linking reactions with other components in the imaging layer to form a three-dimensional cross-linking structure, thereby solving the surface migration problem of infrared absorbers and thermal initiators in the imaging layer. Therefore, the modified cyclodextrin of the present invention forms urethane bond acrylate on cyclodextrin through an amine esterification reaction, and the modified cyclodextrin has high thermosensitive cross-linking activity and wear resistance, and can effectively improve the imaging performance of the unprocessed thermosensitive plate. At the same time, the modified cyclodextrin after imaging can form a three-dimensional network cross-linking structure, which can more effectively solve the surface migration problem of the infrared absorber and the thermal initiator in the imaging layer.

[0020] The cyclodextrin (CD) used in the modified cyclodextrin of the present invention is α-cyclodextrin (α-CD) or β-cyclodextrin (β-CD) or γ-cyclodextrin (γ-CD), and their structures are shown in the following figure:

[0021]

[0022] The cyclodextrin (CD) used in the modified cyclodextrin of the present invention is α-cyclodextrin (α-CD) or β-cyclodextrin (β-CD) or γ-cyclodextrin (γ-CD), and also includes their substitutes, such as their methyl, dimethyl, hydroxypropyl, hydroxyethyl, sulfobutyl, carboxymethyl, glucosyl, piroxithiazide and other group substitutes.

[0023] The isocyanate acrylate (ICA) used in the modified cyclodextrin of the present invention has the following structure:

[0024]

[0025] R 1 is a hydrogen atom or a methyl group, R 2 It is an ester group, an aromatic group, an ether group or a covalent bond, and r is an integer of 1-3.

[0026] Isocyanate acrylate (ICA) is a highly functional bridging intermediate that contains both an isocyanate group and a double bond. Through an amination reaction, its isocyanate group can undergo an amination reaction with the hydroxyl group of cyclodextrin, thereby forming a highly active amination double bond on the cyclodextrin.

[0027] At present, only three isocyanate acrylates (ICA) have been successfully developed and industrialized in the world, namely, ethyl isocyanate acrylate (AOI, CAS registration number: 13641-96-8), ethyl isocyanate methacrylate (MOI, CAS registration number: 30674-80-7) and 2-(2-isocyanoethoxy)ethyl methacrylate (MOI-EG, CAS registration number: 10723-60-9).

[0028] The isocyanate acrylate (ICA) used in the modified cyclodextrin of the present invention is isocyanate ethyl acrylate (abbreviated as AOI, CAS registration number: 13641-96-8) or isocyanate ethyl methacrylate (abbreviated as MOI, CAS registration number: 30674-80-7) or 2-(2-isocyanoethoxy)ethyl methacrylate (abbreviated as MOI-EG, CAS registration number: 10723-60-9).

[0029] The modified cyclodextrin of the present invention is prepared by an amination reaction, and is a product obtained by an amination reaction of cyclodextrin (CD) and isocyanate acrylate (ICA). The amination reaction is a reaction between a hydroxyl group of cyclodextrin (CD) and an isocyanate group of isocyanate acrylate (ICA). The molar number of hydroxyl groups contained in the cyclodextrin (CD) is greater than or equal to the molar number of isocyanate groups contained in the isocyanate acrylate (ICA). The reaction medium is preferably a solvent free of active hydrogen, such as dimethylformamide, dimethylacetamide, etc.; the reaction catalyst is preferably an organic metal compound or an amine, such as stannous octoate, dibutyltin dilaurate, triethylamine, triethylenediamine, etc., and the reaction temperature is preferably 50-100°C.

[0030] A treatment-free thermal plate precursor comprises a carrier and an imaging layer, wherein the imaging layer comprises a hydrophilic thermal sensitive resin, a cross-linkable prepolymer, a modified cyclodextrin, a thermal initiator and an infrared absorber; the modified cyclodextrin is the modified cyclodextrin of the above structure provided in the present application.

[0031] The processing-free heat-sensitive plate precursor of the present invention has an imaging layer in which, by weight percentage, the hydrophilic heat-sensitive resin accounts for 40-80% of the total solid content of the composition, the cross-linkable prepolymer accounts for 10-50% of the total solid content of the composition, the modified cyclodextrin accounts for 5-30% of the total solid content of the composition, the thermal initiator accounts for 1-10% of the total solid content of the composition, and the infrared absorber accounts for 1-10% of the total solid content of the composition.

[0032] The processing-free heat-sensitive plate precursor of the present invention may or may not be provided with a protective layer on the imaging layer, and the protective layer plays an oxygen-blocking and protective role. The protective layer may be made of a water-soluble polymer compound with relatively good crystallinity, such as polyvinyl alcohol, polyvinyl pyrrolidone, hydroxypropyl cellulose, gelatin, gum arabic, polyacrylic acid and other water-soluble polymers.

[0033] The hydrophilic heat-sensitive resin in the imaging layer is described below:

[0034] The imaging layer of the unprocessed thermal plate requires a polymer resin, specifically, a polymer film-forming resin with functional groups. The hydrophilic thermal resin in the imaging layer of the present invention is a functional film-forming resin. In addition to having film-forming properties, which can ensure that the coating liquid of the imaging layer forms a film and adheres to the carrier after drying, this polymer resin also has the special functions of being hydrophilic and thermally sensitive.

[0035] The hydrophilic thermosensitive resin in the treatment-free thermosensitive plate precursor of the present invention is a polyolefin resin having a side chain containing a hydrophilic group and an epoxy group. Furthermore, the hydrophilic thermosensitive resin in the treatment-free thermosensitive plate precursor of the present invention is a polyolefin resin having at least a polyether acrylate or acrylamide hydrophilic copolymer unit and an epoxy acrylate copolymer unit in the copolymer chain.

[0036] As the main resin in the imaging layer of the treatment-free thermal plate, it must first have hydrophilicity. During laser imaging, the uncrosslinked part can be simply pre-cleaned with water or water containing gum, or cleaned under the action of the fountain solution during machine printing to expose the hydrophilic plate base. After the laser heat effect, the crosslinked imaging part forms a three-dimensional network structure due to the crosslinking of the hydrophilic resin and the prepolymer, and the polarity and solubility of the resin change from hydrophilic to hydrophobic. The best way to achieve water solubility of the resin is to directly select a vinyl monomer with a hydrophilic side group as the copolymer unit of the resin. The hydrophilic side groups include carboxyl, hydroxyl, phosphoric acid, sulfonic acid, amino, amide, ether, etc. The hydrophilic thermosensitive resin of the present invention uses a branched polyether or amide group as the hydrophilic group, that is, the hydrophilic thermosensitive resin contains at least a polyether acrylate or acrylamide hydrophilic copolymer unit on the copolymer chain. The hydrophilic copolymer units of polyether acrylate or acrylamide give the hydrophilic thermosensitive resin good self-emulsification, which can make the hydrophilic thermosensitive resin form nano-micron thermoplastic particles. At the same time, the polyether group and acrylamide have good solvent resistance and can resist the erosion of the imaging layer by the monomers in the UV ink.

[0037] In addition, as the main resin in the imaging layer of the treatment-free thermal plate, the resin preferably contains a heat-sensitive group to facilitate thermal imaging. Such imaging groups can be double bonds that can undergo free radical polymerization or epoxy groups that can undergo cationic polymerization, etc. The hydrophilic thermal resin of the present invention contains a heat-sensitive group, and an epoxy group that can undergo cationic polymerization is selected as the photosensitive group, so the resin structural unit contains an epoxy acrylate copolymer unit, and epoxy acrylic monomers such as glycidyl methacrylate and 3,4-epoxycyclohexyl methacrylate can be preferred. Further, epoxy acrylic monomers containing cyclohexyl groups, such as 3,4-epoxycyclohexyl methacrylate, can be preferred. The cyclohexyl group can have better rigidity, and the epoxy group on the cyclohexyl group has a very high activity of cationic polymerization.

[0038] Finally, as the main resin in the imaging layer of the treatment-free thermal plate, the comprehensive properties of the resin, such as rigidity and ink affinity, need to be considered. When the resin is in the form of nano-micron particles and used as an adhesive for the chemical-free thermal plate, the resin preferably contains a thermoplastic structural unit, which is conducive to laser heat-melting film formation. The hydrophilic thermal resin of the present invention is preferably a styrene structural unit. As is known to all, the styrene structural unit has good thermoplasticity and a high glass transition temperature. Styrene copolymers as adhesives for chemical-free thermal CTP plates have the advantages that the heated part is easier to melt, the molecules are arranged more closely, the thermal image part is more solid, and the printing durability of the plate can be increased.

[0039] The hydrophilic thermosensitive resin in the imaging layer of the treatment-free thermal plate can be in the form of a solid, a solution or an emulsion, etc. It is preferably in the form of discrete particles. During thermal imaging, the laser can cause the temperature of the thermoplastic polymer particles in the discrete particle state to undergo agglutination reaction, and the exposed area changes from hydrophilic to hydrophobic and lipophilic.

[0040] The hydrophilic thermosensitive resin of the present invention is synthesized by solution or emulsion copolymerization, and the copolymerization reaction can be random copolymerization or block copolymerization, preferably random copolymerization. The initiator of the polymerization includes peroxides such as di-tert-butyl peroxide, benzoyl peroxide, persulfates such as potassium persulfate, ammonium persulfate, azo compounds such as azobisisobutyronitrile, etc., and the copolymerization method is preferably emulsion polymerization.

[0041] The reaction solvents that can be used include water, alcohols, ketones, esters, ethers and the like or mixtures thereof. The copolymerization temperature is preferably 40-100°C, and optimally 60-90°C.

[0042] The treatment-free heat-sensitive plate precursor of the present invention, wherein the hydrophilic heat-sensitive resin can be preferably a polyolefin resin obtained by copolymerization of styrene, polyethylene glycol acrylate (molecular weight of 2000), methyl methacrylamide ethyl ethylene urea and 3,4-epoxycyclohexyl methacrylate, and the copolymerized units in the hydrophilic heat-sensitive resin are calculated by weight percentage, styrene accounts for 30-70%, polyethylene glycol methyl ether methacrylate (number average molecular weight Mn=2000) accounts for 5-20%, methyl methacrylamide ethyl ethylene urea accounts for 5-20%, and 3,4-epoxycyclohexyl methacrylate accounts for 10-30%. The state is discrete particles with a particle size of 50-200nm.

[0043] The hydrophilic thermosensitive resin in the imaging layer accounts for 40-80% of the total solid content of the composition by weight.

[0044] The cross-linkable prepolymers in the imaging layer are described below:

[0045] The crosslinkable prepolymer in the imaging layer can be a monomer capable of free radical polymerization or a monomer capable of cationic polymerization, etc. The monomer capable of free radical polymerization is generally an acrylic monomer containing a double bond, and the monomer capable of cationic polymerization is generally a monomer containing an epoxy group. The crosslinkable prepolymer in the imaging layer of the present invention is a multifunctional acrylic monomer or a multifunctional polyurethane acrylic monomer, where multifunctionality means that it contains multiple double bonds. Multifunctional acrylic monomers such as 1,6-hexanediol diacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, trimethylolpropane triacrylate, hydroxypropyl glyceryl triacrylate, hydroxyethyl trimethylolpropane triacrylate, polyethylene glycol dimethacrylate, dipentaerythritol hexaacrylate, etc.; multifunctional polyurethane acrylic monomers are condensation products of isocyanates and multifunctional acrylates, such as condensation products of isocyanates with hydroxyethyl acrylate and pentaerythritol triacrylate, etc.; or are condensation products of double-bond-containing isocyanates such as methacryloyloxyisocyanate and polyhydroxy compounds such as pentaerythritol.

[0046] The cross-linkable prepolymer in the imaging layer accounts for 10-50% of the total solid content of the composition by weight.

[0047] The thermal initiators in the imaging layer are described below:

[0048] The plate material has the imaging ability of free radical polymerization, and the thermal initiator is selected from onium salts, such as sulfonium salts, iodonium salts, etc. Under the action of heat, onium salts undergo homolysis and heterolysis simultaneously. The homolysis of onium salts produces free radicals, which triggers free radical polymerization of double bonds in the imaging layer, and the heterolysis of onium salts produces cations, which triggers cationic polymerization of epoxy bonds in the imaging layer. Therefore, the treatment-free thermal plate made with the precursor of the present invention has the dual imaging ability of free radical polymerization and cationic polymerization, and the plate material has excellent imaging ability. The curing of the influence layer can form a network cross-linked structure, and has high wear resistance. Suitable onium salts include sulfonium salts, oxysulfonium salts, oxysulfonium salts, sulfoxide onium salts, diazonium salts and halogen onium salts such as iodonium salts, etc. Specific examples of suitable onium salts include diphenyliodonium chloride, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, [4-[(2-hydroxytetradecyl-oxy]-phenyl]phenyliodonium hexafluoroantimonate, triphenylsulfonium tetrafluoroborate, triphenylsulfonium octylsulfate, 2-methoxy-4-aminophenyldiazonium hexafluorophosphate, phenoxyphenyldiazonium hexafluoroantimonate, and the like. The thermal initiator of the present invention is selected from iodonium salts or sulfonium salts that can undergo homolysis and heterolysis at the same time. Its thermal decomposition temperature is 150-200° C. The thermal initiator accounts for 1-10% of the total weight of the solids of the thermal sensitive layer in the thermal sensitive layer.

[0049] The infrared absorbers in the imaging layer are described below:

[0050] The infrared absorber in the imaging layer of the present invention mainly plays the role of energy transfer. The heat of the infrared laser transfers the laser energy to the thermal initiator through the infrared absorber. The thermal initiator is cracked to generate active groups to make the hydrophilic thermosensitive resin and the cross-linkable prepolymer undergo three-dimensional network polymerization to achieve thermal imaging. The maximum absorption wavelength range of the infrared absorber is 750-1100nm, and it is selected from carbon black, azo dyes, triarylamine dyes, indolium dyes, oxocyanol dyes, cyanine dyes, merocyanine dyes, indocyanine dyes, phthalocyanine dyes, polythiophene dyes, pyrazoline azo dyes, oxazine dyes, naphthoquinone dyes, anthraquinone dyes, quinone imine dyes, methine dyes, porphyrin dyes, etc. In order to improve the platemaking contrast, it is beneficial for the printing operator to check the plate with the naked eye to detect the image defects of the printing plate, and at the same time, it is beneficial for modern highly intelligent printing machines to realize automatic intelligent plate loading through the automatic positioning and recognition of the cross-line images at the four corners of the plate. The selected infrared absorber can be an infrared absorber with a color change function, and the presentation of high-contrast images is achieved through laser cracking. The infrared absorber in the imaging layer of the present invention is preferably a cyanine dye of 750-850 nm.

[0051] The infrared absorber in the imaging layer of the present invention accounts for 1-10% by weight of the total solid content of the composition.

[0052] The carrier in the process-free heat-sensitive plate precursor of the present invention is described in detail below.

[0053] The imaging layer of the present invention needs to be coated on a carrier, and the carrier includes a metal base such as a steel base, a copper base, an aluminum base, and the like.

[0054] The carrier selected by the present invention is an aluminum plate substrate that has been roughened by electrolysis and anodized.

[0055] The aluminum substrate is made by electrolytic roughening, and the average center line roughness is 0.3-0.6um. The aluminum substrate is made of more than 99% aluminum, 0.1%-0.5% iron, 0.03%-0.3% silicon, 0.003% -0.03% copper, and 0.01%-0.1% titanium. The electrolytic roughening electrolyte can be an aqueous solution of acid, alkali or salt. First, place the aluminum plate in an aqueous solution of 1% - 30% sodium hydroxide, potassium hydroxide, sodium carbonate or sodium silicate, etc., and chemically corrode it at a temperature of 20-80°C for 5-250 seconds. Then neutralize it in 10%-30% nitric acid or sulfuric acid at a temperature of 20-70°C to remove the ash. At a temperature of 10-60°C, use a rectangular wave, a mezzanine wave or a sine wave with alternating positive and negative polarity at 5-100A / dm 2 The current density is 10-300 seconds in a nitric acid or hydrochloric acid electrolyte. The aluminum substrate treated by electrolytic roughening is then anodized. Anodization is usually carried out using sulfuric acid, with a concentration of 5-30% sulfuric acid and a current density of 1-15A / dm 2The oxidation temperature is 20-60°C and the oxidation time is 5-250 seconds to form 1-10g / m 2 The aluminum substrate treated by electrolytic roughening and anodizing can be sealed or not. A variety of methods can be used to seal the pores, preferably 50-80% of the volume of the oxide film micropores. For example, a coating thickness of 3 mg / m 2 Polyvinylphosphonic acid seals the micropores of the oxide film.

[0056] The process-free thermal plate precursor of the present invention can be used to manufacture process-free thermal plates, and the process of manufacturing the process-free thermal plates includes at least carrier treatment and imaging layer coating. A protective layer can be coated or not. A protective layer is coated on the imaging layer to reduce the inhibitory effect of oxygen on the performance of the thermal plate imaging layer, and the imaging layer is not polluted or scratched by the external environment. The protective layer can be made of a water-soluble polymer compound with relatively good crystallinity, such as polyvinyl alcohol, polyvinyl pyrrolidone, hydroxypropyl cellulose, gelatin, gum arabic, polyacrylic acid and other water-soluble polymers.

[0057] When the unprocessed heat-sensitive plate is manufactured using the unprocessed heat-sensitive plate precursor of the present invention, other necessary additives may be added, such as solvents, room temperature thermal polymerization inhibitors, surfactants, layer colorants, etc. The solvent is mainly used to prepare the heat-sensitive coating photosensitive liquid from the heat-sensitive composition, including: alcohols, ketones, esters, ethers, amides, aromatic solvents, ethylene dichloride, tetrahydrofuran, etc. The solvent can be used in pure or mixed forms; the room temperature thermal polymerization inhibitor is to prevent the plate from polymerizing at room temperature and improve the room temperature stability of the plate. Thermal polymerization inhibitors include: hydroquinone, nitroxide piperidinol, p-methoxyphenol, di-tert-butyl-p-cresol, pyrogallol, tert-butyl catechol, benzoquinone, 4,4'-thiobis-(3-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-methyl-16-tert-butylphenol), and primary cerium salt of N-nitrosophenylhydroxylamine, etc.; the addition of layer colorants is to increase the image density of the thermal plate after platemaking, so as to facilitate visual inspection or image analysis of the thermal plate after platemaking. The analytical measuring equipment measures the plate properties, which include: methyl violet, ethyl violet, crystal violet, crystal inner violet, Victoria blue, oil green, oil blue, oil yellow, rhodamine B, methyl violet, malachite green, methylene blue, triazines, etc.; surfactants can be added to the coating, and non-ionic surfactants, amphoteric surfactants, silicon-containing surfactants, fluorine-containing surfactants, etc. can be selected, such as betaines, stearic acid glyceryl esters, sorbic acid palm oil esters, polysiloxanes, and polyfluoroalkyl ethers.

[0058] The process-free heat-sensitive plate prepared using the process-free heat-sensitive plate precursor of the present invention is usually coated by techniques known in the art (e.g., knife coating, blade coating, strip coating, roller coating, press coating, etc.).

[0059] The process-free thermal plate made by using the process-free thermal plate precursor of the present invention is scanned and exposed by a thermal CTP plate-making machine, and then washed and developed with water or directly mounted on a printing machine and developed and printed with a fountain solution of the printing machine.

[0060] Beneficial effects of the present invention: The modified cyclodextrin provided in the present application is a product obtained by an amination reaction of cyclodextrin (CD) or a cyclodextrin substitute and isocyanate acrylate (ICA). When used in the imaging layer of a treatment-free thermal plate precursor, since the outer edge (Rim) of the cyclodextrin is hydrophilic and the inner cavity (Cavity) is hydrophobic, it can provide a hydrophobic binding site, which can effectively adsorb infrared absorbers and thermal initiators. At the same time, the modified cyclodextrin after imaging forms a three-dimensional network cross-linked structure, thereby effectively solving the surface migration problem of the infrared absorber and the thermal initiator in the imaging layer; in addition, the modified cyclodextrin forms an amine bond acrylate through an amination reaction, which has high thermal cross-linking activity and wear resistance, and can effectively improve the imaging performance of the treatment-free thermal plate. DETAILED DESCRIPTION

[0061] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that this embodiment is only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Technical personnel skilled in the art can make some non-essential improvements and adjustments based on the above-mentioned contents of the present invention.

[0062] The following are synthesis examples of the present invention, but the present invention is not limited to the following examples.

[0063] Part I: Examples of Synthesis of Modified Cyclodextrin

[0064] Modified cyclodextrins are all synthesized by Lucky Huaguang. The following is the basic synthesis route:

[0065] The main raw materials can be obtained from the following companies: α-cyclodextrin (α-CD), β-cyclodextrin (β-CD), γ-cyclodextrin: all from Zibo Qianhui Biotechnology Co., Ltd.; isocyanate ethyl acrylate (AOI), isocyanate ethyl methacrylate (MOI), 2-(2-isocyanoethoxy)ethyl methacrylate (MOI-EG): Showa Denko K.K., Japan; dibutyltin dilaurate, triethylenediamine: Tianjin Chemical Reagent Plant No. 2; dimethylformamide (DMF) and dimethylacetamide (DMAC): Shanghai Union Carbide Chemical.

[0066] Synthesis of modified cyclodextrin α-CD1:

[0067] In a 500 ml four-necked flask equipped with temperature-controlled heating, mechanical stirring, condensation reflux and nitrogen protection, add 97.3 g of α-cyclodextrin (α-CD), 256 g of ethyl isocyanate acrylate (AOI), 150 g of dimethylformamide (DMF) and 2 g of dibutyltin dilaurate. Stir at 50 °C for 3 hours and cool to terminate the reaction. Then, the target product CD1 is obtained. The reaction stock solution containing the target product can be used directly.

[0068] Synthesis of modified cyclodextrin α-CD2:

[0069] In a 500 ml four-necked flask equipped with temperature-controlled heating, mechanical stirring, condensation reflux and nitrogen protection, add 97.3 g of α-cyclodextrin (α-CD), 15.5 g of ethyl isocyanate methacrylate (MOI), 200 g of dimethylacetamide (DMAC), and 2 g of dibutyltin dilaurate. Stir at 70 °C for 1.5 hours and cool to terminate the reaction. Then, the target product α-CD2 is obtained. The reaction stock solution containing the target product can be used directly.

[0070] Synthesis of modified cyclodextrin α-CD3:

[0071] In a 500 ml four-necked flask equipped with temperature-controlled heating, mechanical stirring, condensation reflux and nitrogen protection, add 97.3 g of α-cyclodextrin (α-CD), 19.5 g of 2-(2-isocyanoethoxy)ethyl methacrylate (MOI-EG), 150 g of dimethylformamide (DMF), and 2 g of dibutyltin dilaurate. Stir at 100 °C for 0.5 hour and cool to terminate the reaction. Then, the target product α-CD3 is obtained. The reaction stock solution containing the target product can be used directly.

[0072] Synthesis of modified cyclodextrin β-CD1:

[0073] In a 500 ml four-necked flask equipped with temperature-controlled heating, mechanical stirring, condensation reflux and nitrogen protection, add 113.5 g of β-cyclodextrin (β-CD), 28.2 g of ethyl isocyanate acrylate (AOI), 150 g of dimethylformamide (DMF) and 2 g of triethylenediamine. Stir at 80 °C for 1.5 hours and cool to terminate the reaction. Then, the target product β-CD1 is obtained. The reaction stock solution containing the target product can be used directly.

[0074] Synthesis of modified cyclodextrin β-CD2:

[0075] In a 500 ml four-necked flask equipped with temperature-controlled heating, mechanical stirring, condensation reflux and nitrogen protection, add 113.5 g of hydroxypropyl β-cyclodextrin (β-CD), 15.5 g of ethyl isocyanate methacrylate (MOI), 150 g of dimethylformamide (DMF), and 2 g of dibutyltin dilaurate. Stir at 90 °C for 1 hour and cool to terminate the reaction. Then, the target product β-CD2 is obtained. The reaction stock solution containing the target product can be used directly.

[0076] Synthesis of modified cyclodextrin β-CD3:

[0077] In a 500 ml four-necked flask equipped with temperature-controlled heating, mechanical stirring, condensation reflux and nitrogen protection, add 113.5 g of carboxymethyl β-cyclodextrin (β-CD), 19.5 g of 2-(2-isocyanoethoxy)ethyl methacrylate (MOI-EG), 150 g of dimethylformamide (DMF), and 2 g of dibutyltin dilaurate. Stir at 80 °C for 1.5 hours and cool to terminate the reaction. Then, the target product β-CD3 is obtained. The reaction stock solution containing the target product can be used directly.

[0078] Synthesis of modified cyclodextrin γ-CD1:

[0079] In a 500 ml four-necked flask equipped with temperature-controlled heating, mechanical stirring, condensation reflux and nitrogen protection, add 129.7 g of γ-cyclodextrin (β-CD), 31 g of ethyl isocyanate acrylate (AOI), 150 g of dimethylacetamide (DMAC) and 2 g of dibutyltin dilaurate. Stir at 60 °C for 3 hours and cool to terminate the reaction. Then, the target product γ-CD1 is obtained. The reaction stock solution containing the target product can be used directly.

[0080] Synthesis of modified cyclodextrin γ-CD2:

[0081] In a 500 ml four-necked flask equipped with temperature-controlled heating, mechanical stirring, condensation reflux and nitrogen protection, add 129.7 g of γ-cyclodextrin (β-CD), 15.5 g of ethyl isocyanate methacrylate (MOI), 150 g of dimethylformamide (DMF), and 2 g of dibutyltin dilaurate. Stir at 70 °C for 1.5 hours and cool to terminate the reaction. Then, the target product γ-CD2 is obtained. The reaction stock solution containing the target product can be used directly.

[0082] Synthesis of modified cyclodextrin γ-CD3:

[0083] In a 500 ml four-necked flask equipped with temperature-controlled heating, mechanical stirring, condensation reflux and nitrogen protection, add 129.7 g of hydroxypropyl γ-cyclodextrin (β-CD), 19.5 g of 2-(2-isocyanoethoxy)ethyl methacrylate (MOI-EG), 150 g of dimethylacetamide (DMAC), and 2 g of stannous octoate. Stir at 80 °C for 1.5 hours and cool to terminate the reaction. Then, the target product γ-CD3 is obtained. The reaction stock solution containing the target product can be used directly.

[0084] Part II: Examples of synthesis of hydrophilic thermosensitive resins (No. A1-A22).

[0085] The main raw materials can be obtained from the following companies: styrene St, methacrylamide ethyl ethylene urea (MAEEU), and isopropyl alcohol are from Shanghai Bailingwei Technology; polyethylene glycol methyl ether methacrylate PEGMA (number average molecular weight Mn=2000) is from Merck Chemical Sigma-Adrich; 3,4-epoxycyclohexyl methacrylate CMA is from Mitsubishi Rayon Chemical Co., Ltd. of Japan; methyl ethyl ketone MEK: Lanzhou Petrochemical, azobisisobutyl cyanide AIBN: Tianjin Fuchen Chemical Reagent.

[0086] Hydrophilic thermosensitive resin A1: Add 75g of deionized water and 250g of isopropanol to a 500ml four-necked flask equipped with temperature control heating, mechanical stirring, condensation reflux and nitrogen protection, raise the temperature to 80°C and start dripping the following mixed solution: 30g (30 wt%) styrene St, 20g (20 wt%) polyethylene glycol methyl ether methacrylate PEGMA (number average molecular weight Mn=2000), 20g (20 wt%) methacrylamide ethyl ethylene urea (MAEEU), 30g (30 wt%) 3,4-epoxycyclohexyl methacrylate, 1g azobisisobutyronitrile, drip for 60 minutes, then react at 80°C for 8 hours, add 0.51g of azobisisobutyronitrile and continue to react for 8 hours, then cool down to end the reaction, and the particle size is 50nm. The reaction stock solution is used directly according to the solid content.

[0087] According to the copolymer unit ratio given in Table 1 and referring to the synthesis process of hydrophilic thermosensitive resin A1, the amount of water and alcohol and the dropping time were adjusted to synthesize hydrophilic thermosensitive resins A1-A22 with different copolymer unit ratios and particle sizes. The particle sizes are shown in Table 1.

[0088] Comparative Example of Synthesis of the Hydrophilic Thermosensitive Resin of the Present Invention Hydrophilic Thermosensitive Resin:

[0089] According to Agfa patent EP 2006-5-24 06114475.4, Agfa polymer F is synthesized. The polymer does not contain hydrophilic groups. The polymer structure is:

[0090]

[0091] Basic operation: add 75g deionized water, 250g isopropanol, and 5g sodium dodecyl sulfate to a 1000 ml four-necked flask with temperature control heating, mechanical stirring, condensation reflux and nitrogen protection device, and add 60g (60 weight%) St (styrene), 40g (40 weight%) AN (acrylonitrile), and 0.7g AIBN (azobisisobutyronitrile) dropwise at 80°C for 0.5 hour. After reacting for 7.5 hours, add 0.3g AIBN (azobisisobutyronitrile) and continue to react for another 12 hours before ending.

[0092] According to Kodak patent US 2005-8-3 11 / 196, Kodak polymer K was synthesized. The polymer contains polyether hydrophilic groups but no epoxy groups. The polymer structure is:

[0093]

[0094] Basic operation: add 75g of deionized water and 250g of n-propanol to a 1000ml four-necked flask equipped with temperature-controlled heating, mechanical stirring, condensation reflux and nitrogen protection device, and add 20g (20 wt%) of St (styrene), 70g (70 wt%) of AN (acrylonitrile), 10g (10 wt%) of PEGMA (polyethoxymethyl acrylate) and AIBN (azobisisobutyronitrile) dropwise at 80°C for 0.5 hour. After reacting for 7.5 hours, add 0.3g of AIBN (azobisisobutyronitrile) and continue to react for another 12 hours before ending.

[0095] Example 1

[0096] Preparation of the plate base: A1050 rolled aluminum plate with a purity of 99.5% and a thickness of 0.3 mm was etched in a 5% sodium hydroxide aqueous solution at 70°C for 20 seconds, rinsed with running water, and immediately neutralized with a 1% nitric acid aqueous solution. Then, in a 1% hydrochloric acid aqueous solution, a sinusoidal alternating current of 50 A / dm was used at 40°C. 2 The surface was electrolytically roughened for 16 seconds at a current density of 10A / dm, then neutralized with a 5% sodium hydroxide aqueous solution at 40°C for 10 seconds and washed with water. Finally, a 20% sulfuric acid aqueous solution was used at 30°C at a current density of 15A / dm 2 The current density was 20 seconds for anodization and then washed with water. The holes were sealed with a 5% sodium silicate aqueous solution at 80°C for 18 seconds, washed with water and dried. The average center line roughness of the plate obtained was 0.5 μm and the oxide film weight was 3.0 g / dm 2 .

[0097] Imaging layer raw materials: Infrared absorbers that meet the requirements of the present invention can be obtained from Dye Chemical or Merck. The infrared absorber (IR820) in the example is Merck product Sigma-Adrich 543365, chemical name: 2-[2-[2-chloro-3-[[1,3-dihydro-1,1-dimethyl-3-(4-sulfonic acid butyl)-2H-benzo[e]indol-2-ylidene]-ethylidene]-1-cyclohexen-1-yl]-vinyl]-1,1-dimethyl-3-(4-sulfonic acid butyl)-1H-benzo[e]indolium hydroxide inner salt; multifunctional acrylate: SR399 is dipentaerythritol pentaacrylate, from Sartomer; multifunctional polyurethane acrylate: PU100 is polyurethane acrylate It is a condensation product of Covestro's Desmodurn 100, hydroxyethyl acrylate and pentaerythritol triacrylate, obtained from Shenyang Institute of Chemical Industry; thermal initiators: diphenyliodonium tetrafluoroborate (code: B1), 4,4-di-tert-butyldiphenyliodonium hexafluorophosphate (code: B2), triphenylsulfonium tetrafluoroborate tetrafluoroborate (code: B3), methyl diphenylsulfonium salt (code: B4) are from J&K, surfactant BYK306 comes from BYK; 1-methoxy-2-propanol comes from Union Carbide Chemical; polyvinyl alcohol PVA-205 comes from Kuraray Co., Ltd. of Japan; polyvinyl pyrrolidone PVPK30 comes from BASF of Germany; emulsifier OP-10 comes from Hamm of Germany.

[0098] Imaging layer raw materials (specific raw materials and amounts are shown in Table 2):

[0099] Hydrophilic thermosensitive resin

[0100] Cross-linkable prepolymer

[0101] Modified Cyclodextrin

[0102] Thermal initiator

[0103] Infrared absorber (IR820)

[0104] The above raw materials were added with 0.5g of surfactant BYK306 and 700g of 1-methoxy-2-propanol to prepare an imaging layer coating solution, which was extruded onto the hydrophilized substrate and dried at 100°C for 60 seconds to obtain 15mg / dm 2 Dry weight of coating.

[0105] The following protective layer can be optionally extrusion coated on the imaging layer and then dried at 110°C for 60 seconds. 2 Dry weight of coating.

[0106] Protective layer formula:

[0107] Polyvinyl alcohol PVA-205 (Japanese Kuraray) 17g

[0108] Polyvinylpyrrolidone PVPK30 (BASF, Germany) 3g

[0109] Emulsifier OP-10 (Helm, Germany) 0.45g

[0110] Deionized water 480g

[0111] Different thermal plates were prepared by the same process as above: the plate base, protective layer, solvent and other necessary additives remained unchanged, and the imaging layer formula was changed according to the data given in Table 2 to prepare Examples 1-22, only Example 1 was coated with a protective layer, and the other examples were not coated with a protective layer. The performance of the thermal plates of the examples is listed in Table 3 below.

[0112] Test and analysis of plate materials:

[0113] Initial: refers to when the plate is just manufactured;

[0114] Forced aging: simulate the natural storage state in a forced way;

[0115] 1. Initial sensitivity: The sensitivity is characterized by the laser energy value required for imaging. If the initiation efficiency of the newly produced plate is low, the energy required for laser imaging is higher. All the newly produced plates mentioned above are placed on a Kodak Thermal CTP platemaker at 5 mJ / cm 2 The progressive amount is between 80-200mJ / cm 2 The plate was exposed within an energy range of , and the initial sensitivity of the plate was measured according to the Pantone LIVE color digital workflow. Its performance is listed in Table 3 below.

[0116] 2. Initial dot quality: Dot quality is characterized by whether 1-99% of the dots can be restored after laser imaging. For example, 1-99% means that 1% to 99% of the dots can be restored, which is the best value. 2-98% means that only 2-98% of the dots can be restored, and 1% and 99% of the dots cannot be restored, which is slightly worse, and so on. The lower the initiation efficiency of the newly produced plate, the higher the 1-100% dots cannot be completely restored. All the above plates were exposed on the Kodak Thermal CTP Platemaking Machine with the best sensitivity energy, and the initial dot restoration value of the image was measured according to the PantoneLIVE color digital workflow. Its performance is listed in Table 3 below.

[0117] 3. Forced aging sensitivity: Forced aging is to simulate the changes of thermal plates during the shelf life under natural storage conditions. All the above plates are placed in a standard thermal plate product packaging box and forced to age for 5 days in an aging box at 40°C and 80% humidity. Then, the plate was tested on a Kodak Thermal CTP platemaker at 5 mJ / cm 2 The progressive amount is between 80-200mJ / cm 2 The plate was exposed within an energy range of , and the sensitivity of the plate was measured according to the Pantone LIVE color digital workflow. Its performance is listed in Table 3 below.

[0118] 4. Forced aging dot quality: Put all the above plates into a standard thermal plate product box, force age them in an aging box at 40℃ and 80% humidity for 5 days, then expose them on a Kodak Thermal CTP platemaking machine with the energy of the best sensitivity, and measure the image dot reproduction value according to the PantoneLIVE color digital workflow. Its performance is listed in Table 3 below.

[0119] 5. Migration rating: Place all the above plates in a standard thermal plate product box and force age them in an aging box at 40°C and 80% humidity for 7 days. The thermal initiator migrates to the surface of the plate. Compared with the newly made sensitive plate, the appearance will be different. The X.rite Pantone eXact scanning spectrophotometer is used to analyze and rate the apparent quality of the thermal plate according to the PantoneLIVE color digital workflow to obtain the migration value, which is scored on a 10-point scale, with 1-10 points, 10 points being the worst and 1 point being the best.

[0120] 6. Printing run: If the iodonium salt initiation efficiency is low and the imaging layer is not fully cured, the printing run of the plate will be reduced; in addition, if the iodonium salt migrates on the surface of the imaging layer, laser exposure will also produce small molecules to break the imaging layer structure, which will also greatly reduce the printing run of the plate. The total number of normal prints printed by the thermal plate was tested using a Heidelberg-XL754C printing press, and its performance is listed in Table 3 below.

[0121] The detection and application results in Table 3 show that the thermal plate manufactured by the thermal plate precursor of the present invention has excellent imaging performance, stability and run length. This is because the modified cyclodextrin contained in the treatment-free thermal plate precursor has a hollow conical cylindrical three-dimensional ring structure, and various organic compounds can be embedded in its hydrophobic cavities, which can effectively adsorb infrared absorbers and thermal initiators. In addition, the modified cyclodextrin can undergo a cross-linking reaction with other components in the imaging layer to form a three-dimensional cross-linking structure, thereby solving the surface migration problem of the infrared absorber and the thermal initiator in the imaging layer; in addition, the modified cyclodextrin of the present invention forms an urethane bond acrylate through an esterification reaction, has high thermal cross-linking activity and wear resistance, and can effectively improve the thermal imaging ability and run length of the treatment-free thermal plate.

[0122] Table 1 Weight percentage of materials and particle size of hydrophilic thermosensitive resin synthesis

[0123]

[0124] Table 2 Example plate imaging layer material feed table (unit: grams)

[0125]

[0126] Table 3 Plate application performance table

[0127]

[0128] The above description is only a preferred embodiment of the present invention, but the protection scope of the present invention is not limited thereto. It should be pointed out that for those skilled in the art and any technician familiar with the technical field, without departing from the overall concept of the present invention, the technical solution and the inventive concept of the present invention are equivalently replaced or changed, and several changes and improvements are made, which should also be regarded as the protection scope of the present invention.

Claims

1. A process-free thermal plate precursor, comprising a carrier and an imaging layer, characterized in that: The imaging layer comprises a hydrophilic thermosensitive resin, a cross-linkable prepolymer, a modified cyclodextrin, a thermal initiator and an infrared absorber; the thermal initiator is an iodonium salt or a sulfonium salt, and the decomposition temperature is 150-220°C; the infrared absorber is a cyanine dye with an absorption peak at 750-850nm; the infrared absorber and the thermal initiator are very easy to migrate in the imaging layer; the hydrophilic thermosensitive resin is a branched polyolefin resin containing a hydrophilic group and an epoxy group; the cross-linkable prepolymer is a multifunctional acrylic monomer or a multifunctional polyurethane acrylic monomer; the modified cyclodextrin is a product obtained by amination reaction of cyclodextrin or a cyclodextrin substitute and isocyanate acrylate; Among them, isocyanate acrylate has the following structure: R 1 is a hydrogen atom or a methyl group, R 2 is an ester group, and r is an integer of 1-3; In the imaging layer, by weight percentage, the hydrophilic thermosensitive resin accounts for 40-80% of the total solid content of the composition, the cross-linkable prepolymer accounts for 10-50% of the total solid content of the composition, the modified cyclodextrin accounts for 5-30% of the total solid content of the composition, the thermal initiator accounts for 1-10% of the total solid content of the composition, and the infrared absorber accounts for 1-10% of the total solid content of the composition.

2. The process-free thermal plate precursor according to claim 1, characterized in that: The cyclodextrin is α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin.

3. The process-free thermal plate precursor according to claim 1, characterized in that: The amination reaction is a reaction between a hydroxyl group of cyclodextrin or a cyclodextrin substitute and an isocyanate group of isocyanate acrylate, and the molar amount of hydroxyl group contained in the cyclodextrin or the cyclodextrin substitute is greater than or equal to the molar amount of isocyanate group contained in the isocyanate acrylate; The isocyanate acrylate is isocyanate ethyl methacrylate, isocyanate ethyl acrylate or 2-(2-isocyanoethoxy)ethyl methacrylate.

4. The process-free heat-sensitive plate precursor according to claim 1 or 3, characterized in that: The reaction medium of the amination reaction is a solvent without active hydrogen, the reaction catalyst is an organic metal compound or amine, and the reaction temperature is 50-100°C.

5. The process-free thermal plate precursor according to claim 1, characterized in that: A protective layer is also provided on the imaging layer.

6. The process-free thermal plate precursor according to claim 1, characterized in that: The hydrophilic thermosensitive resin is a polyolefin resin containing at least a polyether acrylate or acrylamide hydrophilic copolymer unit and an epoxy acrylate copolymer unit in the copolymer chain.

7. The process-free heat-sensitive plate precursor according to claim 6, characterized in that: The hydrophilic thermosensitive resin is a polyolefin resin obtained by copolymerizing styrene, polyethylene glycol methyl ether methacrylate with a number average molecular weight of Mn=2000, methyl acrylamide ethyl ethylene urea and 3,4-epoxycyclohexyl methacrylate; calculated by weight percentage, styrene accounts for 30-70%, polyethylene glycol methyl ether methacrylate with a number average molecular weight of Mn=2000 accounts for 5-20%, methyl acrylamide ethyl ethylene urea accounts for 5-20%, and 3,4-epoxycyclohexyl methacrylate accounts for 10-30%.

8. The process-free thermal plate precursor according to claim 1, characterized in that: The hydrophilic thermosensitive resin is in the form of discrete particles with a particle size of 50-200 nm.

9. The process-free thermal plate precursor according to claim 1, characterized in that: The carrier is an aluminum plate that has been electrolytically roughened and anodized.

10. A treatment-free thermal plate, characterized in that: The method is prepared from the processing-free heat-sensitive plate precursor according to any one of claims 1 to 9.

11. The use of the treatment-free thermal plate according to claim 10, characterized in that: After the thermal plate is scanned and exposed by a thermal CTP plate-making machine, it is washed with water and developed before being mounted on a printing press for printing or directly mounted on a printing press for development and printing with a printing press fountain solution.

Citation Information

Patent Citations

  • Method of making lithographic printing plate and photopolymer composition

    EP0980754A1

  • Thermorecording

    US4004924A

  • Lithographic printing original plate and method for producing the same

    WO1994023954A1

  • Lithographic printing plate precursors for on-press development

    WO2013032780A1

  • Host-guest supramolecular hydrogel, and preparation method and application thereof

    CN107652452A